Application of A4F-MALS for the Characterization of Polymers Prepared by Emulsion Polymerization: Comparison of the Molecular Structure of Styrene-Acrylate and Methyl Methacrylate-Acrylate Copolymers - Podzimek, Štěpán; Machotová, Jana; Zgoni, Hedvika; Boháčik, Peter; Šňupárek, Jaromír (Taylor & Francis Inc, 2016)
In this paper, organic asymmetric flow field flow fractionation coupled to a multi-angle light scattering detector is presented as a very efficient tool for the characterization of copolymers prepared by emulsion polymerization. The molar mass distribution and the extent of branching of styrene-acrylate copolymers have been compared with corresponding copolymers of methyl methacrylate. It has been found that the presence of acrylate monomer results in the increase of molar mass and formation of branched macromolecules due to intermolecular chain transfer to polymer similarly as in case of methyl methacrylate-acrylate copolymers. However, the effect is far less pronounced.
Využití A4F-MALS pro charakterizaci polymerů připravených emulzní polymerací: srovnání molekulární struktury kopolymerů na bázi styren-akrylátů a methylmethakrylát-akrylátů
Keywords: Branching; emulsion polymerization; intrinsic viscosity; latex; light scattering; molecular weight distribution; separation techniques; Separační techniky; rozptyl světla; emulzní polymerace; kopolymer; latex; větvení; vnitřní viskozita; distribuce molekulové hmotnosti